Oxygen saturation and perfusion index from pulse oximetry in adult volunteers with viable incisors. (3rd July 2016) - Kong, Hyoun-Joong; Shin, Teo Jeon; Hyun, Hong-Keun; Kim, Young-Jae; Kim, Jung-Wook; Shon, Won-Jun
Abstract: Objective: Evaluation of pulp vitality is an important diagnostic procedure in dentistry. Conventional techniques for measurement of pulp vitality, including thermal stimulation, electrical stimulation, or direct dentin stimulation, are frequently associated with false positive or false negative results. Recently, oxygen saturation from pulse oximetry has been utilized in the evaluation of pulp vitality. Perfusion index (PI) data calculated from photoplethysmography have been widely used to evaluate peripheral perfusion. The combination of oxygen saturation and PI may aid in the accurate measurement of pulp vitality. We aimed to investigate the baseline values of oxygen saturation and PI using pulse oximetry in adult volunteers. Material and methods: Fifteen adult volunteers with viable incisors were tested. To measure PI, a fabricated oxygen sensor was applied to an incisor without a pulp lesion while oxygen saturation was simultaneously measured in the finger. Oxygen saturation and PI were continuously measured with customized software. The normal reference values of oxygen saturation and PI were obtained by analyzing the recorded data. Results: Pulse oximetry showed relatively stable, objective, and accurate oxygen saturation results. The tooth oxygen saturation ranged from 97% to 100%. The PI ranged from 0.3% to 0.5%, and PI and oxygen saturation showed relatively consistent values across subjects. Conclusions: Although there are some limitations to our study, these results may prove useful for detecting teeth with impaired vitality and non-invasively differentiating between necrotic and vital pulp.